Interactions between Primary Neurons and Graphene Films with Different Structure and Electrical Conductivity. (13th September 2020) - Capasso, Andrea; Rodrigues, João; Moschetta, Matteo; Buonocore, Francesco; Faggio, Giuliana; Messina, Giacomo; Kim, Min Jung; Kwon, Junyoung; Placidi, Ernesto; Benfenati, Fabio; Bramini, Mattia; Lee, Gwan‐Hyoung; et al.
Abstract: Graphene‐based materials represent a useful tool for the realization of novel neural interfaces. Several studies have demonstrated the biocompatibility of graphene‐based supports, but the biological interactions between graphene and neurons still pose open questions. In this work, the influence of graphene films with different characteristics on the growth and maturation of primary cortical neurons is investigated. Graphene films are grown by chemical vapor deposition progressively lowering the temperature range from 1070 to 650 °C to change the lattice structure and corresponding electrical conductivity. Two graphene‐based films with different electrical properties are selected and used as substrate for growing primary cortical neurons: i) highly crystalline and conductive (grown at 1070 °C) and ii) highly disordered and 140‐times less conductive (grown at 790 °C). Electron and fluorescence microscopy imaging reveal an excellent neuronal viability and the development of a mature, structured, and excitable network onto both substrates, regardless of their microstructure and electrical conductivity. The results underline that high electrical conductivity by itself is not fundamental for graphene‐based neuronal interfaces, while other physico–chemical characteristics, including the atomic structure, should be also considered in the design of functional, bio‐friendly templates. This finding widens the spectrum of carbon‐based materials suitable for neuroscience applications. Abstract : The influence of the different characteristics of graphene‐based films on the growth and maturation of primary cortical neurons is investigated. The results suggest that high electrical conductivity by itself is not a necessary condition for the realization of an efficient neuronal interface, while other physical–chemical characteristics of the graphene‐based film, such as the atomic structure, are to be considered.